FORMING PEDAGOGICAL RESPONSIBILITY AND ADAPTABILITY OF TEACHERS OF SPECIALIZED EDUCATIONAL ORGANIZATIONS FOR CHILDREN WITH DISABILITIES - Mavjuda Ashurovna Tilakova (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, pedagogical innovations in special education, the professional activity of special education specialists, issues of the introduction of the inclusive education system in the Republic of Uzbekistan, increasing the market activity and management efficiency of educational institutions, inclusive education development processes, pedagogical activities issues such as the development of activity efficiency have been touched upon in their studies.